Implementation of Government Regulation Number 45 of 1990 Concerning Divorce Permits for Civil Servants in the Regional Government of North Barito Regency - Asla Eva Setya (Journal of Social Research, 2025)
This study aims to analyze the implementation of Government Regulation Number 45 of 1990 concerning divorce permits for Civil Servants (PNS) within the Regional Government of North Barito Regency. This research is motivated by the continued large number of State Civil Apparatus (ASN) who file for divorce without going through the permit mechanism according to the provisions, as well as the less than optimal implementation of the regulation at the regional level. The method used is empirical legal research with a sociological juridical approach, through interviews with ASN, the BKPSDM, and the Muara Teweh Religious Court. The results of the study indicate that the process of issuing Decrees (SK) permitting divorce by the Regent in North Barito Regency is inconsistent, with a time span varying from two weeks to two years. This difference is caused by the absence of Standard Operating Procedures (SOP), the issuance of Circular Letters or Regent Regulations that regulate the technical implementation of the PP, and weak coordination between agencies in the implementation of mediation as stipulated in Article 6 of PP Number 45 of 1990 in conjunction with PP Number 10 of 1983. In addition, the mediation process often does not run effectively due to the lack of presence of related parties, so that the purpose of the regulation to prevent early divorce and maintain harmony in ASN households has not been achieved. Based on these findings, this study recommends the preparation of SOPs and Regent Regulations regarding ASN divorce permits, increasing legal socialization for ASN, and strengthening the role of BKPSDM as a supervisor of the implementation of regulations in order to create an effective, transparent, and fair licensing system in accordance with the principle of benefit in Islamic law.